The Influence of Leadership Style, Motivation and Training on Non-ASN Job Satisfaction at the Medan Helvetia Sub-district Office - Evi Beatric Dewi Zebua; Teguh Wahyono; Samrin Samrin (Utan Kayu Publishing, 2025)
Non-ASN personnel have an important role in supporting public services at the sub-district level, but often face various challenges related to irregular employment status and limitations in career development. This study aims to analyze the influence of leadership style, motivation, and training on the job satisfaction of non-ASN personnel at the Medan Helvetia Sub-district Office, both partially and simultaneously. The research method used is quantitative research with an associative approach. The research population is all non-ASN personnel at the Medan Helvetia Sub-district Office which totals 144 people. The number of samples was determined using the Slovin formula with an error rate of 10% so that a sample of 59 respondents was obtained which was selected using the incidental sampling technique. Data collection is carried out through questionnaires that have been tested for validity and reliability. The data analysis technique used multiple linear regression analysis with the help of SPSS software. The results of the study show that: (1) Leadership style has a positive and significant effect on job satisfaction; (2) Motivation has a positive but insignificant effect on job satisfaction; (3) Training has a positive and significant effect on job satisfaction; (4) Leadership style, motivation, and training simultaneously have a positive and significant effect on job satisfaction. An R² value of 0.929 indicates that all three independent variables are able to explain 92.9% of the variation in job satisfaction, while the remaining 7.1% is explained by other variables outside the research model